2016
DOI: 10.1093/bja/aev416
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative factors associated with acute kidney injury after partial nephrectomy

Abstract: Potentially modifiable factors associated with AKI in the postoperative period were identified as baseline renal function, preoperative hypertension, longer duration of surgical time and ischaemia time, and warm ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
52
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 19 publications
9
52
4
Order By: Relevance
“…We also found that, in the short term, further significant factors influencing the postoperative evolution of renal function were male sex (HR, 31.401), albumin levels (HR, 0.010), and ECOG score (0 and 1, HR < 1.0), which were previously reported as factors affecting renal function [1618]. Patients with good nutritional status and general performance in the preoperative stage are expected to have good baseline renal function and postoperative recovery after PN [16].…”
Section: Discussionsupporting
confidence: 71%
“…We also found that, in the short term, further significant factors influencing the postoperative evolution of renal function were male sex (HR, 31.401), albumin levels (HR, 0.010), and ECOG score (0 and 1, HR < 1.0), which were previously reported as factors affecting renal function [1618]. Patients with good nutritional status and general performance in the preoperative stage are expected to have good baseline renal function and postoperative recovery after PN [16].…”
Section: Discussionsupporting
confidence: 71%
“…Patients undergoing surgery for a renal tumor are at high risk for AKI because of the nephron loss involved in the surgical procedures for renal tumors. Some studies have shown several factors associated with AKI after PN . Among them, renal ischemia is one of the most important.…”
Section: Discussionmentioning
confidence: 94%
“…Rajan et al (13) found that 39% of his patients had ARF after partial nephrectomy. However, Thompson et al (5) and Weight et al (6) reported that 60% of patients had some type of kidney dysfunction after surgery.…”
Section: Discussionmentioning
confidence: 99%